2016
DOI: 10.5966/sctm.2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Free Transplantation of Patient-Derived Induced Pluripotent Stem Cell Progeny for Customized Islet Regeneration

Abstract: Transplantation of progenitors from induced pluripotent stem cells reprogrammed by lentiviral vectors led to the formation of invasive teratocarcinoma-like tumors in more than 90% of immunodeficient mice. Combined transgene-free reprogramming and elimination of residual pluripotent cells by enzymatic dissociation ensured tumor-free transplantation, ultimately enabling regeneration of type 1 diabetes-specific human islet structures in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…As summarized in Table , multiple reports describe the generation of iPSCs from patients with diabetes‐related disorders, including types 1 and 2 diabetes mellitus; maturity‐onset diabetes of the young types 1, 2, 3, 5 and 8, in which a single gene mutation causes diabetes; and mitochondria diabetes. A report analyzing maturity‐onset diabetes of the young type 2 showed that iPSC models can reproduce the disease phenotype caused by mutations in a glucokinase gene that cause a decrease in insulin secretion by glucose stimulation.…”
Section: Disease Modeling and Drug Discoverymentioning
confidence: 99%
“…As summarized in Table , multiple reports describe the generation of iPSCs from patients with diabetes‐related disorders, including types 1 and 2 diabetes mellitus; maturity‐onset diabetes of the young types 1, 2, 3, 5 and 8, in which a single gene mutation causes diabetes; and mitochondria diabetes. A report analyzing maturity‐onset diabetes of the young type 2 showed that iPSC models can reproduce the disease phenotype caused by mutations in a glucokinase gene that cause a decrease in insulin secretion by glucose stimulation.…”
Section: Disease Modeling and Drug Discoverymentioning
confidence: 99%
“…Before iPSCs can be considered for clinical application newer methods that have been developed using non‐integrating systems must be applied in these species to reduce the risk of the reprogramming factors becoming re‐activated and leading to tumor formation by the cells. Recent work has demonstrated that the generation of mouse iPSCs through non‐integrating methods (along with efficient removal of undifferentiated cells prior to transplantation) reduces the risk of tumor formation .…”
Section: Differentiation Of Companion Animal Pluripotent Cells Into Tmentioning
confidence: 99%
“…For example, Doi et al found that, when using ESC‐derived neural cells, remaining undifferentiated ESCs induced tumor formation when grafted into monkey brains . A separate group found that, when progenitors of iPSCs reprogrammed with lentiviral vectors were transplanted into immunodeficient mice, more than 90% of the recipient animals formed invasive teratocarcinoma‐like tumors . Conversely, tumor‐free transplantation was achieved via the combination of transgene‐free reprogramming as well as the elimination of residual stem cells .…”
Section: Introductionmentioning
confidence: 99%